Case Report: Extreme Levels of Serum S-100B in a Patient with Chronic Subdural Hematoma - Persson, Malin E.; Thelin, Eric P.; Bellander, Bo-Michael (Frontiers in Neurology, 2012)
The protein S-100B is a biomarker increasingly used within neurosurgery and neurointensive care. As a relatively sensitive, yet unspecific, indicator of CNS pathology, potential sources of error must be clearly understood when interpreting serum S-100B levels. This case report studied the course of a 46-year-old gentleman with a chronic subdural hemorrhage, serum S-100B levels of 22 μg/l, and a history of malignant melanoma. Both intra- and extra-cranial sources of S-100B are evaluated and imply an unclear contribution of several sources to the total serum concentration. Potential sources of error when interpreting serum concentrations of S-100B are discussed.